The pharmacokinetics of peginterferon lambda‐1a following single dose administration to subjects with impaired renal function. (22nd July 2015) - Hruska, Matthew W.; Adamczyk, Robert; Colston, Elizabeth; Hesney, Michael; Stonier, Michele; Myler, Heather; Bertz, Richard
Abstract Aims This open label study was conducted to assess the effect of renal impairment (RI) on the pharmacokinetics (PK) of peginterferon lambda‐1a (Lambda). Methods Subjects (age 18–75 years, BMI 18–35 kg m–2) were enrolled into one of five renal function groups: normal (n = 12), mild RI (n = 8), moderate RI (n = 8), severe RI (n = 7), end‐stage renal disease (ESRD, n = 8) based on estimated glomerular filtration rate (eGFR) calculated using the Modification of Diet in Renal Disease (MDRD) equation. Subjects received a single dose of Lambda (180 µg) subcutaneously on day 1 followed by PK serum sample collections through day 29. Safety, tolerability and immunogenicity data were collected through day 43. PK parameters were estimated and summarized by group. Geometric mean ratios (GMR) and 90% confidence intervals (CIs) were calculated between normal and RI groups. Results With decreasing eGFR, Lambda exposure (Cmax, AUC) increased while apparent clearance (CL/F) and apparent volume of distribution (V/F) decreased. Relative to subjects with normal renal function (geometric mean AUC = 99.5 ng ml–1 h), Lambda exposure estimates (AUC) were slightly increased in the mild RI group (geometric mean [90% CI]: 1.20 [0.82, 1.77]) and greater in the moderate (1.95 [1.35, 2.83]), severe RI (1.95 [1.30, 2.93]) and ESRD (1.88 [1.30, 2.73]) groups. Lambda was generally well tolerated. Conclusions The results demonstrated that RI reduces the clearance of Lambda and suggests that dose modifications may not be required in patients with mild RI but may be required in patients with moderate to severe RI or ESRD.